Soft Nationalization: How the US Government Will Control AI Labs - Cheng, Deric; Katzke, Corin (SuperIntelligence - Robotics - Safety & Alignment, 2024)
We have yet to see anyone describe a critical element of effective AI safety planning: a realistic model of the upcoming role the US government will play in controlling frontier AI. The rapid development of AI will lead to increasing national security concerns, which will in turn pressure the US to progressively take action to control frontier AI development. This process has already begun1, and it will only escalate as frontier capabilities advance. However, we argue that existing descriptions of nationalization2 along the lines of a new Manhattan Project3 are unrealistic and reductive. The state of the frontier AI industry — with more than 1 trillion4 in private funding, tens of thousands of participants, and pervasive economic impacts — is unlike nuclear research or any previously nationalized industry. The traditional interpretation of nationalization, which entails bringing private assets under the ownership of a state government5, is not the only option available. Government consolidation of frontier AI development is legally, politically, and practically unlikely. We expect that AI nationalization won't look like a consolidated government-led “Project”, but rather like an evolving application of US government control over frontier AI labs. The US government can select from many different policy levers to gain influence over these labs, and will progressively pull these levers as geopolitical circumstances, particularly around national security, seem to demand it. Government control of AI labs will likely escalate as concerns over national security grow. The boundary between "regulation" and "nationalization" will become hazy. In particular, we believe the US government can and will satisfy its national security concerns in nearly all scenarios by combining sets of these policy levers, and would only turn to total nationalization as a last resort. We’re calling the process of progressively increasing government control over frontier AI labs via iterative policy levers soft nationalization. AUTHOR’S NOTE It’s important to clarify that we are not advocating for a national security approach to AI governance, nor yet supporting any individual policy actions. Instead, we are describing a model of US behavior that we believe is likely to be accurate to improve the effectiveness of AI safety agendas.